Aktivitas Antioksidan Ekstrak Daun Cengkeh (ANTIOKSIDANT ACTIVITY OF CLOVE LEAF EXTRACT) - Mu’nisa, Andi; Wresdiyati, Tutik; Kusumorini, Nastiti; Manalu, Wasmen (Jurnal Veteriner; Vol 13 No 3 (2012), 2013)
Antioxidant activity of clove leaf was investigated. The clove leaves (Eugenia aromatica) wereprepared with reflux extraction using methanol, water, and ethanol. Total activities of the extractsand reducing power were measured with thiocyanate method and reducing potential method. Resultshowed that the highest total antioxidant activity was observed in methanol extract. It appearsthat the ability of this extract for partitioning at the interface of emulsion in tested oxidationsystem was the highest among the other extracts, therefore it had the best activity to inhibitoxidation. The type of phenolic compounds of this extract appeared to be responsible for the highestradical scavenging capacity. The same phenomenon occurred for reducing power, methanol extracthad the highest reducing power, thereby suggesting that each extracts comprised different type ofphenol based on different polarity of reflux used for extraction. Total antioxidant activity and thehighest reducing power obtained from methanol extract. Both are closely related to total phenolcontent of the clove leaves.
Keywords: Eugenia aromatica, total antioxidant activity, total phenol, reducing power